Concept analysis of self-efficacy among schizophrenia - Rahmawati, Ashri Maulida; Sawitri, Dian Ratna; Dwidiyanti, Meidiana; Rahman, Ainun Najib Febrya (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
The concept of self-efficacy is a core development concept of social cognitive theory. Self-efficacy is needed by schizophrenia patients to overcome problems. The initiation aims are to analyze concepts and clarify the conceptual meaning of self-concepts for schizophrenic patients. Walker and Avant's concept analysis procedure was used in this administration. A Literature review was carried out using online databases such as Science Direct, PubMed, EBSCO, and Proquest with the keywords "Schizophrenia" and "Self Efficacy". The concept of self-efficacy is important for schizophrenic patients to be confident in their ability to solve problems and achieve goals. This is preceded by the concept of self-efficacy in schizophrenia: outcome expectations, efficacy expectations, and outcome values. Concept attribute: efficacy in negative symptoms, social interactions, and efficacy in positive symptoms. The consequences of the concept: changes in behavior and performance. Patients with a high level of efficacy can produce good behavior and performance to overcome both positive and negative symptoms. Abstrak: Konsep efikasi diri merupakan pengembangan konsep inti dari teori social cognitive. Efikasi diri dibutuhkan oleh pasien skizofrenia untuk mengatasi masalah. Tujuan dari penulisan ini adalah untuk menganalisis konsep dan mengklarifikasi makna dari konsep efikasi diri bagi pasien skizofrenia. Prosedur analisis konsep dari Walker dan Avant digunakan dalam penulisan ini. Literature review dilakukan menggunakan database online seperti Science Direct, PubMed, EBSCHO dan Proquest dengan kata kunci “Schizophrenia” dan “Self Efficacy”. Konsep efikasi diri penting untuk pasien skizofrenia agar dapat yakin akan  kemampuan nya untuk mengatasi masalah dan mencapai tujuan. Antecedent dari konsep efikasi diri pada skizofrenia: Outcome expectancy, Efficacy expectancy,  dan outcome value. Atribut konsep: efikasi dalam gejala negatif, efikasi dalam  interaksi sosial dan efikasi dalam gejala positif. Konsekuensi dari konsep: perubahan perilaku dan kinerja. Pasien dengan tingkat efikasi yang tinggi dapat menghasilkan perilaku dan kinerja yang baik untuk mengatasi baik gejala positif dan negative.